2019
DOI: 10.1212/wnl.0000000000007250
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of acute cerebral microinfarcts in vascular cognitive impairment

Abstract: ObjectiveTo determine the occurrence of acute cerebral microinfarcts (ACMIs) in memory clinic patients and relate their presence to vascular risk and cognitive profile, CSF and neuroimaging markers, and clinical outcome.MethodsThe TRACE-VCI study is a memory clinic cohort of patients with vascular brain injury on MRI (i.e., possible vascular cognitive impairment [VCI]). We included 783 patients (mean age 67.6 ± 8.5, 46% female) with available 3T diffusion-weighted imaging (DWI). ACMIs were defined as supratent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
4
18
1
Order By: Relevance
“…A possible limitation of the study is that we obtained a measure of overall CBF at the level of the large extracranial arteries using two-dimensional phase-contrast MRI and did not measure CBF at the tissue level. Yet, the observed mean CBF values in our study are comparable to other studies that did use measures at the tissue level [1][2][3][4][5][6][7][8][9][10][11][12][13]. This does not exclude that there can be regional areas of abnormal perfusion at the site where lesions develop or have developed.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A possible limitation of the study is that we obtained a measure of overall CBF at the level of the large extracranial arteries using two-dimensional phase-contrast MRI and did not measure CBF at the tissue level. Yet, the observed mean CBF values in our study are comparable to other studies that did use measures at the tissue level [1][2][3][4][5][6][7][8][9][10][11][12][13]. This does not exclude that there can be regional areas of abnormal perfusion at the site where lesions develop or have developed.…”
Section: Discussionsupporting
confidence: 83%
“…We found no relationship between CBF and MBs or lacunes after correction for age and sex in our primary or secondary analyses. A limited number of studies, both cross-sectional and longitudinal, have assessed the association between CBF and these features of SVD [5][6][7][8][9][10][11][12][13]. A single study on MBs, in a rather small and selected population of patients with symptomatic SVD, did show a relationship between multiple MBs (5 or more) and lower CBF in one of several brain regions tested [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recurrent stroke risk is difficult to predict, as most CMIs cannot be detected via magnetic resonance imaging. Recently, it has been reported that diffusion-weighted imaging can detect and monitor acute CMIs for a month, which may provide a better intervention window (Auriel, Westover et al, 2015, Ferro, van den Brink et al, 2019. In this study, we found that a single CMI could induce epigenetic alterations (H3K4me1 and H3K4me3) in the contralateral side, suggesting that a single CMI may have a big impact on the brain at the epigenetic level.…”
Section: Discussionsupporting
confidence: 49%
“…These symptoms have a negative impact on the daily life of patients with VCI. 4 With the gradual increase in VCI patients, effective treatments are more and more urgent. Many studies have been devoted to the neuroinflammation and oxidative stress owing to chronic inflammation and long-term cerebrovascular dysfunction deficiency in cognitive altered process; these studies focused on endothelium and neuronal disruption acting as a promoter of neurodegenerative events.…”
Section: Introductionmentioning
confidence: 99%